The Relationship between DKPP and PTUN Decisions regarding Ethical Violation by General Election Administrators - Ahmad Siboy; Dewi Cahyandari (Jurnal Konstitusi, 2022)
The commissioner of the general election administration was discharged through the decision of the General Election Administrator Honorary Council (DKPP). The decision is not final and binding at the executive branch, considering that the decision can be cancelled by the Administrative Court. This study aims to define the authority of DKPP and PTUN in resolving ethical violations committed by election administrators and parse the implications and relationships of the decisions of the two institutions. This paper also proposes an ideal concept for the design of solving ethical violations of election administrators in the future. This study uses normative juridical methods. The results showed that the DKPP and PTUN have overlapping authority but with different decisions. DKPP purely adjudicates ethical issues, and the Administrative Court adjudicates the Presidential Decree, which is a follow-up to the DKPP decision. To avoid conflicting decisions on cases that intersect, violations of the code of ethics in the future must be resolved with a settlement mechanism by the judiciary.